Analisis Bibliometrik dan Spasial Border Fiscal Cost Premium Menggunakan VOSviewer - Sunaryono Sunaryono; Maria Christiana Iman Kalis; M Irfani Hendri (LPPM STMIK El Rahma Yogyakarta, 2026)
Border regions often face higher public service delivery costs due to geographic isolation, limited accessibility, and inadequate infrastructure. Although research on fiscal equalization, regional inequality, and border studies has expanded significantly, existing studies remain fragmented and lack a comprehensive conceptual framework for understanding fiscal compensation needs in border areas. This study aims to analyze the development of the literature and propose the concept of Border Fiscal Cost Premium through a Systematic Literature Review (SLR) and bibliometric analysis using VOSviewer. The dataset consists of 82 peer-reviewed articles indexed in Scopus from 2001 to 2025. The results identify four major research clusters: Regional Economy and Border Relations, Infrastructure Investment and Economic Development, Fiscal Equalization and Public Finance, and Border Governance and Spatial Inequality. Temporal analysis reveals growing attention to themes such as accessibility, public services, demography, and territorial disadvantage. The literature synthesis indicates that additional fiscal costs in border regions are driven by geographic isolation, limited connectivity, institutional fragmentation, constrained fiscal capacity, and interregional coordination challenges. The proposed Border Fiscal Cost Premium serves as a conceptual framework integrating fiscal, spatial, and governance dimensions to support more adaptive, equitable, and place-based fiscal transfer policies for border regions.